2016
DOI: 10.1038/srep22784
|View full text |Cite
|
Sign up to set email alerts
|

NECAB3 Promotes Activation of Hypoxia-inducible factor-1 during Normoxia and Enhances Tumourigenicity of Cancer Cells

Abstract: Unlike most cells, cancer cells activate hypoxia inducible factor-1 (HIF-1) to use glycolysis even at normal oxygen levels, or normoxia. Therefore, HIF-1 is an attractive target in cancer therapy. However, the regulation of HIF-1 during normoxia is not well characterised, although Mint3 was recently found to activate HIF-1 in cancer cells and macrophages by suppressing the HIF-1 inhibitor, factor inhibiting HIF-1 (FIH-1). In this study, we analysed Mint3-binding proteins to investigate the mechanism by which M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 35 publications
1
29
1
Order By: Relevance
“…(39) Mint3 is ubiquitously expressed, although some cancer cells express the protein at relatively higher levels. (53) However, Mint3 does not inhibit FIH-1 when MT1-MMP is absent. Genetic depletion of Mint3 (Mint3-KO) in mice does not exhibit severe phenotypes, except for macrophages that exhibit an ATP shortage, similarly to MT1-KO cells.…”
Section: Mt1-mmp Employs Mint3/apba3 To Inhibit Fih-1mentioning
confidence: 99%
See 3 more Smart Citations
“…(39) Mint3 is ubiquitously expressed, although some cancer cells express the protein at relatively higher levels. (53) However, Mint3 does not inhibit FIH-1 when MT1-MMP is absent. Genetic depletion of Mint3 (Mint3-KO) in mice does not exhibit severe phenotypes, except for macrophages that exhibit an ATP shortage, similarly to MT1-KO cells.…”
Section: Mt1-mmp Employs Mint3/apba3 To Inhibit Fih-1mentioning
confidence: 99%
“…Mint3 is ubiquitously expressed, although some cancer cells express the protein at relatively higher levels . However, Mint3 does not inhibit FIH‐1 when MT1‐MMP is absent.…”
Section: Mt1‐mmp Employs Mint3/apba3 To Inhibit Fih‐1mentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently reported that the monooxygenase NECAB3 and mTOR signalling also promote Mint3-mediated HIF-1 activation in cancer cells4445. Although whether NECAB3 relates to inflammation is unclear, mTOR contributes to inflammatory responses4647.…”
Section: Discussionmentioning
confidence: 99%